Two kitchens, one home a multiple case study on the existence of two kitchens in selected Filipino middle class homes - Querijero, Erika Nicole M.
ABSTRACT This study is an attempt to determine whether or not selected Filipino middle class households with two kitchens, namely the clean and dirty kitchens, utilize them according to their spatial functions in cooking and food preparation. The reasons as to why there are two kitchens in the selected Filipino middle class homes were identified and evaluated. A multiple-method type of research was utilized in data gathering involving the use of personal interviews, onsite observations, site measurements and photo-documentation. Fifteen Filipino middle class families were chosen as respondents through the use of Snowball Sampling. The respondents were then further screened based on the following criteria: (1) respondent family must have two kitchens, specifically a clean kitchen and a dirty kitchen; (2) respondent family must belong to the Middle Class sector. There were five respondent families from Mataas na Kahoy, Batangas, another five from Baler, Aurora, four respondent families from Cainta, Rizal and one respondent family from Marikina City. Through the use of the Theory of Proxemics (Hall, 1969), space utilization and design of both the kitchens were analyzed. The results of the study suggest that Filipino socio-cultural concepts have a bearing on the families' use of the clean and dirty kitchens. Specifically, the Filipino concepts of loob at labas (inside and outside) and harap at likod (front and back) (Fajardo, 1995) surfaced throughout the duration of the interviews and onsite observations. These Filipino concepts refer to the hierarchy of spaces which are determined by the user. The findings re-affirm the notion of public and private spaces in relation to the clean and dirty kitchens as found in Mayo's study (2004). The clean kitchen remains to be seen as a public space where visitors are allowed to view and enter while the dirty kitchen as a private space where only household members are allowed to enter. The location and material finishes of the two kitchens also indicated the treatment of the spaces. Aside from psychological factors, results showed that the physical needs relating to spatial functions of the respondent families were fulfilled because of having two kitchens. The study proposes that more researches pertaining to Filipino food preparation and cooking practices should be conducted to provide additional knowledge which can further be used in designing Filipino kitchen spaces.